2010
DOI: 10.1159/000321675
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic Differences in Dementia Epidemiology: Global and Asia-Pacific Perspectives

Abstract: The burden of dementia will continue to rise globally, particularly in developing countries, many of which lie in the Asia-Pacific region. It was initially thought that both prevalence and incidence of dementia showed little geographic variation. More recent work has suggested differences: migrant populations attain rates between their homelands and adopted countries, and higher rates have been found in African Americans and Hispanics compared to Caucasian Whites, and also among native Australians. The only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 79 publications
3
44
0
1
Order By: Relevance
“…Secondly, once in contact with the point of care, diagnostic evaluation of dementia in immigrant patients can be particularly complicated because of communication problems, often requiring the use of interpreters, and due to a lack of appropriate assessment tools, especially for immigrants with low levels of education [15,16,17]. Thirdly, the epidemiology of the disease might also differ among immigrant groups [18]. A registry-based study from Denmark found that dementia was under-diagnosed among ethnic minorities ≥60 years old but over-diagnosed in those ≤60 years old [19].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, once in contact with the point of care, diagnostic evaluation of dementia in immigrant patients can be particularly complicated because of communication problems, often requiring the use of interpreters, and due to a lack of appropriate assessment tools, especially for immigrants with low levels of education [15,16,17]. Thirdly, the epidemiology of the disease might also differ among immigrant groups [18]. A registry-based study from Denmark found that dementia was under-diagnosed among ethnic minorities ≥60 years old but over-diagnosed in those ≤60 years old [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, even population-based studies permit limited generalization to the overall population, particularly in developing countries, where sociodemographic and economic characteristics vary widely [5,6,7,8]. As a result, current descriptions of the prevalence of dementia in such contexts are of little help to policymakers in introducing health care measures.…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian contingent is highly admixed, with roughly 60-75% of its ancestry derived from Iberian whites, 10-30% from West Africans, and 5-20% from Native Americans [18,19]. Studies worldwide have linked AD to ethnic differences between populations [20,21], including recent work suggesting that migrant populations attain rates between those of their homelands and adopted countries [22]. However, few association trials performed with Brazilian AD patients have considered genetic ancestry estimates as main or accessory variables when investigating markers for this complex phenotype.…”
Section: Introductionmentioning
confidence: 99%